AMBIVALENSI PERILAKU MAHASISWA SANTRI DALAM ERA GLOBALISASI - Suhermanto Suhermanto (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
College Student, is a community of intellectual candidates who will become leaders in the future, the successor of leadership in his era later. Therefore it is fitting to get all of us attention with guidance, direction, and others including by introducing them to the real world that full of challenges, not to mention the students who are in the sub-culture of the pesantren. Although pesantren itself was initially only an entity to deepen the sciences of Islamic science, but in further development, due to its flexibility, and the demands of the people's need for "formal" things, pesantren did not leave the characteristics of independence, simplicity, istikhoroh, considering the aspects of benefits-mafsadah, maslahah-mudorot, began to accept the entry of formal schools, from elementary to college level. And there it is a challenge for the pesantren to prepare a generation that is not behind the times. Globalization, is an inevitable process of the world, will enter and penetrate to all corners of the world no matter how small its form. Therefore, this last term becomes important to be introduced to the pesantren community especially among students, namely students who are studying at university level, not to be surprised to see the future that will and must be faced. Hopefully.